Maternal Kangaroo care education program in the neonatal intensive care unit improved mothers' perceptions, knowledge, perceived barriers and stress relates to premature infant - Sharmiza Samsudin; Ping Lei Chui; Azanna Binti Ahmad Kamar; Khatijah Lim Abdullah (Wiley, 2023)
Abstract Aim To assess the effectiveness of the maternal kangaroo care education programme over 1 month and 3 months on the mother's perception, knowledge, perceived barriers and stress. Design A quasi‐experimental and longitudinal study was conducted among mothers with premature infants. Methods Forty‐eight mother‐infant dyads were enrolled per arm in the control and experimental groups. The control group received standard routine care, while the experimental group received a maternal kangaroo care education program. Data were collected through self‐administered Kangaroo Care Questionnaires. Chi‐square, the general linear model and repeated measures ANOVA were used to analyse data. Results The demographics are a majority of Malay mothers with multipara, a caesarean delivery with prematurity. At 3 months post‐intervention, the experimental group reported a significant reduction in stress, a positive perception and good knowledge towards kangaroo care implementation. The mothers' perceived barriers towards kangaroo care significantly decreased after 3 months in the experimental group.